The Role of Jambi Malay Traditional Institutions in the Seloko Oral Traditions of the Jambi Culture in Maintaining the Advancement of Culture - Muhammad Dwi Kurniadi; Zulkarnain Zulkarnain (BIRCU, 2021)
The purpose of writing this scientific article is to gain an understanding of the oral tradition of the Javanese traditional seloko adat used in Javanese Malay weddings, whose problem formulation includes: (1) What is the oral tradition? (2) What is Jambi adat seloko? (3) How are the efforts of the Jambi provincial customary institutions to maintain the advancement of culture? To answer these three problems the writer used a qualitative approach with the literature study method that collected several articles from previous research and conducted interviews with several cultural figures in Jambi Province. From this research, it was found that one of the 10 elements of culture, namely the oral tradition, is found in Jambi under the name Seloko where it is an oral tradition that contains advice, guidelines for life.